Hearing Damage Through Blast - Reichenbach,T (2016)
Hearing damage through blast is an escalating problem in the military: it accounted for 25 % of all injuries during Operation Iraqi Freedom in 2004 and was accordingly the most common single injury [1]. Auditory dysfunction in general is now the most prevalent individual service-connected disability, with compensation estimated to exceed $2.2 billion in 2014 in the U.S.A [2, 3]. A recent report on Royal Marines returning from deployment in Afghanistan has found that two-thirds sustained severe and permanent hearing damage [4, 5].